2019
DOI: 10.1371/journal.pone.0222266
|View full text |Cite
|
Sign up to set email alerts
|

Rural pipeline and willingness to work in rural areas: Mixed method study on students in midwifery and obstetric nursing in Mali

Abstract: The availability and retention of healthcare professionals in rural areas and remote areas is a challenge to the health sector worldwide. Attracting people who are most likely to be interested in rural practice can be conducive to the sustainable availability of health services in rural areas where health facilities are typically understaffed and existing professionals often underqualified. This article aims to contribute to the rural pipeline evidence, and reports on the findings of a study that investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
1
6
0
1
Order By: Relevance
“… 11 Also, longitudinal observations of pipeline participants’ performance and character create opportunity to assess their ability to succeed in advanced health professional education aside from use of standardized tests. 16 , 34 , 35 , 36 , 37 This alternative assessment could offset an unintentional exclusion of capable rural, minority, and nontraditional students that is linked to such tests. 33 These local reforms could be evaluated based on their effects on the health of targeted underserved rural populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 11 Also, longitudinal observations of pipeline participants’ performance and character create opportunity to assess their ability to succeed in advanced health professional education aside from use of standardized tests. 16 , 34 , 35 , 36 , 37 This alternative assessment could offset an unintentional exclusion of capable rural, minority, and nontraditional students that is linked to such tests. 33 These local reforms could be evaluated based on their effects on the health of targeted underserved rural populations.…”
Section: Discussionmentioning
confidence: 99%
“…15 Pipeline programs have reported success with outcomes including attitudes, intentions, admission, performance, specialty choice, and practice location. 16 Those evaluations took institutional perspectives that may not resonate with local community leaders. It is important that programs demonstrate and articulate the value of medical education reforms that construct pipeline programs in ways that engage these leaders and their influence in political processes.…”
mentioning
confidence: 99%
“…This study tried to evaluate the job performance of medical graduates trained by CSP, while most existing studies focused on attraction and retention [20,[41][42][43][44]. We found that CSP graduates have demonstrated good job performance in primary health settings in China.…”
Section: Discussionmentioning
confidence: 99%
“…In Nigeria, there is acute shortage and inappropriate distribution of radiographers. The availability and retention of healthcare professionals in rural areas is a challenge to the health sector globally [1].…”
Section: Introductionmentioning
confidence: 99%
“…In Nigeria, there is acute shortage and inappropriate distribution of radiographers. The availability and retention of healthcare professionals in rural areas is a challenge to the health sector globally [1]. Radiographers, like other health professionals prefer to work in urban areas due to higher incomes, good career opportunities, good infrastructures and social amenities [2,3].…”
Section: Introductionmentioning
confidence: 99%